A Contribution to Active Infrared Laser Spectroscopy for Remote Substance Detection - Jarvis, Jan-Philip (Schriftenreihe Automatische Sichtprüfung und Bildverarbeitung, 2017)
In this work we present a stand-off, long wave infrared (LWIR) spectroscopy system for remote detection of hazardous substances. The principle is based upon wavelength selective illumination using External Cavity Quantum Cascade Lasers, that are tunable in the LWIR wavelength range from 7.5 - 10 µm, in which most chemical substances exhibit a highly characteristic absorption behaviour.